2022
DOI: 10.1186/s43088-022-00224-0
|View full text |Cite
|
Sign up to set email alerts
|

Rydberg energies and transition probabilities of Li I for np–ms (m ≤ 5) transitions

Abstract: Background Mathematical modeling provides grounds for understanding scientific systems theoretically. It serves as a guide for experimentalists in determining directions of investigation. Recently, the Covid-19 pandemic has caused disturbances in almost every walk of life. Scientists have played their role and have continued research on the effects of the pandemic. Various mathematical models have been used in different branches of science (Djilali et al. in Phys Scr 96 12 124016, 2021; Math Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…The cooper minimum was first observed for alkali atoms. It occurs due to overlapping the positive and negative amplitude of the wavefunctions of the levels taking part in the transition [16]. Due to this, the dipole matrix elements have zero or a minimum value for a particular set of principal quantum numbers of both levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooper minimum was first observed for alkali atoms. It occurs due to overlapping the positive and negative amplitude of the wavefunctions of the levels taking part in the transition [16]. Due to this, the dipole matrix elements have zero or a minimum value for a particular set of principal quantum numbers of both levels.…”
Section: Discussionmentioning
confidence: 99%
“…The reason could be its closeness to the core, which may affect the effective charge compared to the other levels that lie relatively far from the core. It was observed in the calculations of transition probability and lifetimes of the same configuration in Li I [16], Be II [17], and C IV [18] that the calculated and experimental values are slightly different. For the configuration 1s 2 2p in Li-like atoms and ions, one should expect a slight difference in theoretical and experimental lifetimes.…”
mentioning
confidence: 99%
“…Hence Schrodinger equation for hydrogen atoms can be used for such atoms and ions with the approximation that all other electrons in the inner shells together with the nucleus form the core, like the hydrogen atom, e.g., hydrogen-like atoms and ions are Li I, Be II, B III, C IV, N V, and O VI. The theory used in this work is the same as in [22]. The Schrodinger equation for hydrogen-like atoms and ions is given by,…”
Section: Theorymentioning
confidence: 99%
“…The group also reported transition probability of Lithium atom and lithium like ions by using the same theory [14][15][16][17][18][19]. In 2022, R. Siddiq et al studied the four series of Li, by using WBEPMT they calculated energies and transition probabilities of the series [20]. Saeed et al evaluated transition probabilities and lifetimes of the lithium levels, and found new lifetimes using polynomial of each of the ns, np, nd and nf series [21].…”
Section: Introductionmentioning
confidence: 99%